Methodical guidelines for Completing Assignments in "Foreign Language" - Netetska, T. M.; Neustroeva, G. O.; Rubtsova, V. V. (National Technical University "Kharkiv Polytechnic Institute", 2025)
The methodological guidelines are intended for independent extracurricular work of 4th-year students of economic, computer and humanitarian specialties and are aimed at developing the learning skills necessary for students to successfully master the grammar sections provided for in the syllabus of the foreign language course. The methodological guidelines consist of seven options for training tests and are intended to prepare the student for the final test. They contain educational linguistic material that corresponds to the program content of the modules studied during the 8th semester within the framework of the discipline "Foreign Language". Each section contains exercises and tasks for training skills in recognizing and using grammatical phenomena, review and familiarization reading, etc.
Keywords: methodical guidelines; foreign language; grammar; linguistics; educational process